2019
DOI: 10.1111/liv.14315
|View full text |Cite
|
Sign up to set email alerts
|

In‐field evaluation of Xpert® HCV viral load Fingerstick assay in people who inject drugs in Tanzania

Abstract: Background Although novel hepatitis C virus (HCV) RNA point‐of‐care technology has the potential to enhance the diagnosis in resource‐limited settings, very little real‐world validation of their utility exists. We evaluate the performance of HCV RNA quantification using the Xpert® HCV viral load Fingerstick assay (Xpert® HCV VL Fingerstick assay) as compared to the World Health Organisation pre‐qualified plasma Xpert® HCV VL assay among people who inject drugs (PWID) attending an opioid agonist therapy (OAT) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 31 publications
1
27
0
Order By: Relevance
“…In the present study, despite the collection of specimens by trained phlebotomists such errors were observed. Similar errors varying from 1-20 % had also been reported previously [9,10]. With our experience, a slightly deeper prick led to sufficient volume to be collected, thereby minimizing error.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the present study, despite the collection of specimens by trained phlebotomists such errors were observed. Similar errors varying from 1-20 % had also been reported previously [9,10]. With our experience, a slightly deeper prick led to sufficient volume to be collected, thereby minimizing error.…”
Section: Discussionsupporting
confidence: 88%
“…The results are in concordance with a previous published study by Lamoury et al ., who also reported 100 % sensitivity and specificity [9]. A recent study conducted on people who inject drugs in Tanzania recorded 99.1 % sensitivity and 98.7 % specificity [10]. Unlike previous studies, the present study also evaluated performance using different sample types, i.e.…”
Section: Discussionmentioning
confidence: 97%
“…If this structure is the closest to ‘real‐world’ networks then the TasP effects of targeting HCV treatment at individuals with the largest numbers of injecting partnerships may have been underestimated. Such an approach is practically possible by engaging PWID with HCV treatment via peer‐led referral, 33 and the increasing availability of point of care RNA testing will support monitoring for reinfection in high risk PWID 34,35 …”
Section: Discussionmentioning
confidence: 99%
“…The second uses GeneXpert to provide point-of-care viral load testing. Similar applications of GeneXpert have achieved success in HIV programs in limited-resource settings, as they allow patients to receive viral load results on the same day as sample collection (19), and have been successfully used in HCV pilot programs in Egypt (29), Indonesia (30), and Tanzania (31). Given that HCV GeneXpert is WHO pre-quali ed for HCV viral load testing, it provides an opportunity for improving HCV patients monitoring and would also allow for integrated multi-disease testing platforms (32).…”
Section: Discussionmentioning
confidence: 99%